William Rowan Hamilton and the Poetry of Science - Tomalin, Marcus (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2009)
AbstractThis article explores the scientific and literary work of William Rowan Hamilton (1805-1865). Hamilton was recognised as one of the finest scientists of his generation, and he made lasting contributions to the discipline that eventually became known as ‘physics’. In addition, though, he was fascinated by the relationship between mathematics and poetry. He wrote extensively about this subject, and, from 1827 onwards, he sustained a close friendship with Wordsworth who provided detailed critical analyses of Hamilton’s own poems. Influenced by these revealing exchanges, Hamilton identified poetical qualities in physical and mathematical treatises, and this article probes his views concerning these perceived interconnections with reference to other ‘Romantic’ scientists such as Humphry Davy. In particular, Hamilton’s striking claim that a text such as Joseph-Louis Lagrange’s Mécanique Analytique (1788) can be viewed as ‘a kind of scientific poem’ is assessed.